Is social connectedness still in decline after the Covid-19 pandemic? Cohort trends in secondary school students in Finland between 2017 and 2023 - Read, Sanna; Kiuru, Noona; Helenius, Jenni; Junttila, Niina; Salmela-Aro, Katariina (BioMed Central, 2026)
Several previous cohort studies suggest declining social connectedness in young people since 2000, the pattern accelerated during the covid-19 pandemic. Little is known whether social connectedness had recovered to the pre-pandemic levels. We investigated whether the declining pattern in experienced social connectedness in secondary school students between 2017 and 2021 changed in 2023. We also investigated the role of individual and school characteristics in these trends. We used nationally representative Finnish data of students in lower and upper secondary education (analytic n = 556,424–557,391). Social connectedness was measured by number of close friends, feelings of loneliness and sense of belonging at school. Regression analyses included the fixed effects and the interactions of year, gender, school level, parental education, immigration status of the student and urban-rural location. The results showed that the overall declining trend of social connectedness between 2017 and 2021 slowed down between 2021 and 2023: number of close friends further declined at a slower rate (1% decline), while there was no change in sense of belonging at school and a slight recovery (2% reduction) in feelings of loneliness. In some subgroups, such as students in general upper secondary schools and students with immigration background had a faster recovery than other student groups. The results point to little overall improvement in social connectedness in secondary school students in Finland after the pandemic.